The Influence of Top Management Team Competencies on Strategic Decision-Making in Hospital - Widaya, Theodorus Adrianto; Adisasmito, Wiku (Jurnal Health Sains, 2025)
Top management team (TMT) competencies are pivotal in navigating hospitals’ strategic challenges, yet their collective impact remains underexplored amid evolving healthcare complexities. This narrative review synthesizes 15 studies (2010–2025) to analyze how TMT competencies—leadership, communication, strategic thinking, and adaptability—shape strategic decision-making and identifies gaps in cross-cultural applicability. A systematic search across PubMed, Scopus, and ScienceDirect employed PICO criteria, prioritizing peer-reviewed empirical studies. Data were analyzed thematically, integrating quantitative and qualitative findings. TMT competencies significantly enhance decision-making quality, particularly in resource-limited settings. Key themes include: (1) team synergy outweighing individual prowess, (2) adaptive training as a critical enabler, and (3) unmet needs for context-specific competency frameworks. The study underscores the urgency of developing culturally tailored training programs and leveraging mixed-methods research to optimize TMT effectiveness. Policymakers and hospitals must prioritize competency integration to foster resilient, patient-centered leadership.